Composite film and preparation method thereof, light-emitting device and preparation method thereof, and display device
By arranging a perovskite material modification layer on the surface of the inorganic nanoparticle layer of the electroluminescent device, the problem of gap defects in the inorganic nanoparticle layer is solved and the electrical performance of the device is improved.
Patent Information
- Application Number
- CN202310884742.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-18
- Publication Date
- 2025-01-21
AI Technical Summary
There are gap defects in the inorganic nanoparticle layer in electroluminescent devices, resulting in a degradation of device performance.
A modification layer is provided on the surface of the inorganic nanoparticle layer. The material of the modification layer includes a perovskite material. At least some of the ligands are connected to the modification layer to fill gap defects in the inorganic nanoparticle layer through chemical bonds.
Improve the flatness and stability of the inorganic nanoparticle layer, and improve the electrical performance of the luminous device.
Smart Images

Figure CN119342978A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of light-emitting devices, and in particular to a composite film and a preparation method thereof, a light-emitting device and a preparation method thereof, and a display device. Background Art
[0002] Electroluminescent devices include OLED (Organic Light-Emitting Diode) and QLED (Quantum Dot Light Emitting Diodes). QLED has the advantages of high color saturation, wet process preparation and high stability, which has attracted more and more attention in the research of QLED. OLED has a wide range of applications in display, lighting, smart wearable and other fields due to its good self-luminous properties, high contrast, fast response and flexible display.
[0003] An inorganic nanoparticle layer is usually provided in an electroluminescent device to improve carrier transport. However, gap defects usually exist in the inorganic nanoparticle layer, which results in degradation of device performance. Summary of the invention
[0004] Based on this, the embodiments of the present application provide a composite film and a method for preparing the same, a light-emitting device and a method for preparing the same, and a display device.
[0005] In a first aspect, an embodiment of the present application provides a composite film, comprising a stacked inorganic nanoparticle layer and a modified layer, wherein the material of the modified layer comprises a perovskite material;
[0006] The inorganic nanoparticle layer includes an inorganic nanomaterial and a ligand connected to the surface of the inorganic nanomaterial, and at least part of the ligand is connected to the modified layer.
[0007] In some embodiments, at least a portion of the ligands are attached to the modified layer via chemical bonds.
[0008] In some embodiments, the structural formula of the perovskite material is ABX3, wherein A is a monovalent organic cation or a monovalent metal cation, B is a divalent metal cation, and X is a halogen ion; the monovalent organic cation is a methylamine ion or a formamidine ion, the monovalent metal cation is a cesium ion or a rubidium ion, and the divalent metal cation is a lead ion or a tin ion.
[0009] In some embodiments, the structural formula of the perovskite material is ABX3, wherein A is a monovalent organic cation, and the monovalent organic cation is a methylamine ion; and / or
[0010] B is a divalent metal cation, and the divalent metal cation is a lead ion; and / or
[0011] The structural formula of the perovskite material is CH3NH3PbX3.
[0012] In some embodiments, the ligand has a structural formula of RCOOH, wherein R is selected from an alkyl group, an alkenyl group, an alkynyl group or an aromatic group having 1 to 30 carbon atoms; and / or
[0013] The ligand includes at least one of acetic acid, propionic acid, butyric acid, valeric acid, oleic acid, lauric acid, myristic acid, palmitic acid and stearic acid.
[0014] In some embodiments, the inorganic nanomaterial is selected from at least one of metal oxides, doped metal oxides, II-VI semiconductor materials, III-V semiconductor materials, and I-III-VI semiconductor materials; and / or
[0015] The metal oxide is selected from at least one of ZnO, BaO, TiO2, SnO2; and / or
[0016] The metal oxide in the doped metal oxide is selected from at least one of ZnO, TiO2, and SnO2, and the doping element is selected from at least one of Al, Mg, Li, In, and Ga; and / or
[0017] The II-VI semiconductor material is selected from at least one of ZnS, ZnSe and CdS; and / or
[0018] The III-V semiconductor material is selected from at least one of InP and GaP; and / or
[0019] The Group I-III-VI semiconductor material is selected from at least one of CuInS and CuGaS.
[0020] In some embodiments, the thickness ratio of the inorganic nanoparticle layer to the modified layer is (60-80):(1-8).
[0021] In a second aspect, an embodiment of the present application provides a method for preparing a composite film, comprising:
[0022] providing a substrate;
[0023] forming an inorganic nanoparticle layer on the substrate, wherein the inorganic nanoparticle layer comprises an inorganic nanomaterial and a ligand connected to the surface of the inorganic nanomaterial;
[0024] A modification layer is formed on the inorganic nanoparticle layer, wherein the material of the modification layer includes a perovskite material, and at least part of the ligands are connected to the modification layer.
[0025] In some embodiments, at least a portion of the ligands are connected to the modified layer via chemical bonds; and / or
[0026] The structural formula of the perovskite material is ABX3, wherein A is a monovalent organic cation or a monovalent metal cation, B is a divalent metal cation, and X is a halogen ion; the monovalent organic cation is a methylamine ion or a formamidine ion, the monovalent metal cation is a cesium ion or a rubidium ion, and the divalent metal cation is a lead ion or a tin ion.
[0027] In some embodiments, forming a modified layer on the inorganic nanoparticle layer comprises: applying a perovskite material solution on the inorganic nanoparticle layer to form a modified layer; and / or
[0028] The perovskite material solution includes a perovskite material solution and a first solvent.
[0029] In some embodiments, the concentration of the perovskite material solution is 0.3 mg / ml to 0.8 mg / ml; and / or
[0030] The structural formula of the perovskite material is ABX3, wherein A is a monovalent organic cation or a monovalent metal cation, B is a divalent metal cation, and X is a halogen ion; the monovalent organic cation is a methylamine ion or a formamidine ion, the monovalent metal cation is a cesium ion or a rubidium ion, and the divalent metal cation is a lead ion or a tin ion; and / or
[0031] The first solvent includes at least one of N,N-dimethylformamide and dimethyl sulfoxide.
[0032] In some embodiments, forming a modification layer on the inorganic nanoparticle layer further comprises: after forming the modification layer, annealing the modification layer, the annealing temperature is 70° C. to 90° C., and the annealing time is 6 minutes to 14 minutes.
[0033] In some embodiments, forming an inorganic nanoparticle layer on the substrate comprises: applying an inorganic nanomaterial solution on the substrate to form an inorganic nanoparticle layer; and / or
[0034] The inorganic nanomaterial solution comprises an inorganic nanomaterial and a second solvent, and a ligand is connected to the surface of the inorganic nanomaterial; and / or
[0035] The concentration of the inorganic nano material solution is 20 mg / ml to 40 mg / ml; and / or
[0036] The second solvent comprises at least one of an alcohol compound, N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide and acetonitrile; and / or
[0037] The alcohol compound includes at least one of methanol, ethanol and isopropanol.
[0038] In some embodiments, forming the inorganic nanoparticle layer on the substrate further comprises: after forming the inorganic nanoparticle layer, annealing the inorganic nanoparticle layer, the annealing temperature is 70° C. to 90° C., and the annealing time is 3 minutes to 8 minutes.
[0039] In a third aspect, an embodiment of the present application provides a light emitting device, including:
[0040] bottom electrode;
[0041] An inorganic nanoparticle layer, disposed on one side of the bottom electrode, the inorganic nanoparticle layer comprising an inorganic nanomaterial and a ligand connected to the surface of the inorganic nanomaterial;
[0042] A modification layer is disposed on a side of the inorganic nanoparticle layer away from the bottom electrode, wherein the material of the modification layer includes a perovskite material, and at least part of the ligands are connected to the modification layer through chemical bonds;
[0043] A top electrode is disposed on a side of the modified layer away from the inorganic nanoparticle layer;
[0044] Wherein, the bottom electrode is a cathode, the top electrode is an anode, and the light-emitting device further comprises a light-emitting layer disposed between the modified layer and the top electrode; or
[0045] The bottom electrode is an anode, the top electrode is a cathode, and the light-emitting device further comprises a light-emitting layer disposed between the bottom electrode and the inorganic nanoparticle layer.
[0046] In some embodiments, when the bottom electrode is an anode and the top electrode is a cathode, the light-emitting device further comprises a hole injection layer and a hole transport layer disposed between the bottom electrode and the light-emitting layer, wherein the hole injection layer is disposed close to the bottom electrode and the hole transport layer is disposed close to the light-emitting layer; or
[0047] When the bottom electrode is a cathode and the top electrode is an anode, the light-emitting device further comprises a hole injection layer and a hole transport layer arranged between the top electrode and the light-emitting layer, wherein the hole injection layer is arranged close to the top electrode, and the hole transport layer is arranged close to the light-emitting layer.
[0048] In some embodiments, the material of the hole transport layer includes 4,4'-N,N'-dicarbazolyl-biphenyl, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl))-biphenyl aniline), N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(N-vinylcarbazole) and its derivatives, N,N'-bis(1-naphthyl)-N ,N'-diphenyl-1,1'-biphenyl-4-4'-diamine, poly(phenylene vinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene], poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene], 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene, 4,4'-cyclohexylbis[N,N-di(4-methylphenyl)aniline] , 1,3-di(carbazole-9-yl)benzene, polyaniline, polypyrrole, poly(p-)phenylene vinylene, aromatic tertiary amines, polynuclear aromatic tertiary amines, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraarylbenzidine, poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, polyspirofluorene and its derivatives, polythiophene and its derivatives; and / or
[0049] The material of the hole injection layer includes at least one of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid and its derivatives, copper phthalocyanine, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, poly(dioxyethylthiophene), 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine, tetracyanoquinodimethane, transition metal oxides and transition metal sulfur compounds; and / or
[0050] The cathode and the anode are independently selected from a doped metal oxide particle electrode, a composite electrode, a graphene electrode, a carbon nanotube electrode, a metal single substance electrode or an alloy electrode, the material of the doped metal oxide particle electrode includes one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide, the composite electrode includes AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS or ZnS / Al / ZnS, and the material of the metal single substance electrode includes one or more of Ag, Al, Cu, Mo, Au, Pt, Ca, Mg and Ba; and / or
[0051] The material of the light-emitting layer includes at least one of an organic light-emitting material and a quantum dot light-emitting material, and the organic light-emitting material includes one or more of 4,4'-bis(N-carbazole)-1,1'-biphenyl:tri[2-(p-tolyl)pyridine iridium(III), 4,4',4"-tri(carbazole-9-yl)triphenylamine:tri[2-(p-tolyl)pyridine iridium, diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, 1,4,7,10-tetra-tert-butyl perylene, rubrene derivatives, thermally activated delayed fluorescence materials, exciplex light-emitting materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives;The quantum dot luminescent material comprises at least one of a single structure quantum dot and a core-shell structure quantum dot, the material of the single structure quantum dot, the core material of the core-shell structure quantum dot and the shell material of the core-shell structure quantum dot each comprise at least one of a II-VI group compound, a IV-VI group compound, a III-V group compound and a I-III-VI group compound, and the II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnS At least one of CdS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, Pb At least one of SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, and SnPbSTe, and the III-V compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, and AlNSb , AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, and the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2. ;
[0052] In a fourth aspect, an embodiment of the present application provides a method for preparing a light-emitting device, comprising:
[0053] Providing a light-emitting device preform, wherein the light-emitting device preform comprises a bottom electrode;
[0054] forming an inorganic nanoparticle layer on the light-emitting device preform, wherein the inorganic nanoparticle layer comprises an inorganic nanomaterial and a ligand connected to the surface of the inorganic nanomaterial;
[0055] forming a modification layer on the inorganic nanoparticle layer, wherein the material of the modification layer includes a perovskite material, and at least part of the ligands are connected to the modification layer through chemical bonds;
[0056] forming a top electrode on the modified layer to obtain a light-emitting device;
[0057] Wherein, the bottom electrode is a cathode, the top electrode is an anode, and forming the top electrode on the modified layer comprises: forming a light-emitting layer on the modified layer, and forming the top electrode on the light-emitting layer; or
[0058] The bottom electrode is an anode, the top electrode is a cathode, and the light-emitting device preform further includes a light-emitting layer formed on the bottom electrode.
[0059] In some embodiments, when the bottom electrode is an anode and the top electrode is a cathode, the light-emitting device preform further includes a hole injection layer and a hole transport layer, the hole injection layer is disposed close to the bottom electrode, and the hole transport layer is disposed close to the light-emitting layer; or
[0060] When the bottom electrode is a cathode and the top electrode is an anode, forming the top electrode on the modified layer includes: forming a hole transport layer on the light-emitting layer, forming a hole injection layer on the hole transport layer, and forming the top electrode on the hole injection layer.
[0061] In a fifth aspect, an embodiment of the present application provides a display device, comprising a light-emitting device as described above or a light-emitting device manufactured by the manufacturing method as described above.
[0062] The composite film provided in the embodiment of the present application, by setting a modification layer on the surface of the inorganic nanoparticle layer, makes at least part of the ligands in the inorganic nanoparticle layer connected to the modification layer, utilizes the modification layer to improve the gap defects in the inorganic nanoparticle layer, and then improves the flatness of the inorganic nanoparticle layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for describing the embodiments.
[0064] Figure 1 A schematic diagram of the structure of the composite film provided in an embodiment of the present application.
[0065] Figure 2 A schematic diagram of the first structure of the light-emitting device provided in an embodiment of the present application.
[0066] Figure 3 A second structural schematic diagram of the light-emitting device provided in an embodiment of the present application.
[0067] Figure 4 A flow chart of a method for preparing a light-emitting device provided in an embodiment of the present application.
[0068] Figure 5 Schematic diagram of the structure of the light-emitting device in comparative example 1. DETAILED DESCRIPTION
[0069] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of this application.
[0070] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0071] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c" can all mean: a, b, c, a+b, a+c, b+c, or a+b+c, where a, b, c can be single or multiple, respectively.
[0072] In the present application, when another layer is formed "on" a certain layer, the so-called "on" is a broad concept, which may indicate that the formed another layer is adjacent to the certain layer, or may indicate that there are other spacing structural layers between the another layer and the certain layer. For example, when a second electrode is formed "on" the first carrier functional layer, the so-called "on" may indicate that the formed second electrode is adjacent to the first carrier functional layer, or may indicate that there are other spacing structural layers between the second electrode and the first carrier functional layer, such as a light-emitting layer.
[0073] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0074] See also Figure 1 The embodiment of the present application first provides a composite film 90, comprising an inorganic nanoparticle layer 30 and a modified layer 20 stacked, wherein the material of the modified layer 20 comprises a perovskite material;
[0075] The inorganic nanoparticle layer 30 includes inorganic nanomaterials and ligands connected to the surfaces of the inorganic nanomaterials, and at least part of the ligands are connected to the modified layer 20 .
[0076] Exemplarily, at least part of the ligands are connected to the modification layer 20 via chemical bonds.
[0077] Exemplarily, the structural formula of the perovskite material is ABX3, wherein A is a monovalent organic cation or a monovalent metal cation, B is a divalent metal cation, and X is a halogen ion.
[0078] Exemplarily, the monovalent organic cation is methylamine ion (CH3(NH)2 + , M.A. + ) or formamidinium ion (HC(NH2)2 + , F.A. + ), the monovalent metal cation is cesium ion (Cs + ) or rubidium ion (Rb + ), the divalent metal cation is lead ion or tin ion.
[0079] Exemplarily, the structural formula of the perovskite material is ABX3, wherein A is a monovalent organic cation, and the monovalent organic cation is a methylamine ion;
[0080] B is a divalent metal cation, and the divalent metal cation is a lead ion.
[0081] The methylamine ions and lead ions are selected as monovalent cations and divalent cations in the perovskite material, respectively, which can maintain the long-term chemical stability and performance of the modified layer material. - ), chloride ion (Cl - ), bromide ion (Br- ), iodide ion (I - ) or astatine ion (At - ).
[0082] In some embodiments, the structural formula of the perovskite material is CH3NH3PbX3. The ion size of methylamine ions and lead ions is relatively small, and the two have good compatibility and interaction. When they are selected simultaneously in the perovskite material, the interstitial defects on the surface of the inorganic nanoparticle layer 30 can be filled and a stable lattice structure can be formed, thereby improving the surface flatness of the inorganic nanoparticle layer 30 and improving the stability of the composite film 90.
[0083] Exemplarily, the structural formula of the ligand can be RCOOH, wherein R is selected from a C1-C30 alkyl group, a C2-C30 alkenyl group, a C2-C30 alkynyl group, or an aromatic group having 5 to 40 ring atoms. In some embodiments, the ligand includes at least one of acetic acid, propionic acid, butyric acid, valeric acid, oleic acid, lauric acid, myristic acid, palmitic acid, and stearic acid. Exemplarily, the number of carbon atoms in R can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, etc.
[0084] Exemplarily, the chemical reaction formula between the ligand and the perovskite material is as follows:
[0085] (CH3NH3)PbX3+RCOOH→(CH3NH3)Pb(RCOO)X2+HX.
[0086] Exemplarily, the perovskite material may include at least one of methylamine lead iodide (FAI), methylamine lead fluoride, methylamine lead chlorine and methylamine lead bromine, wherein the structural formula of methylamine lead iodine is CH3NH3PbI3, the structural formula of methylamine lead fluorine is CH3NH3PbF3, the structural formula of methylamine lead chlorine is CH3NH3PbCl3, and the structural formula of methylamine lead bromine is CH3NH3PbBr3.
[0087] In some embodiments, the perovskite material is methylamine lead iodide (CH3NH3PbI3), and the chemical reaction formula between the ligand and the perovskite material is as follows:
[0088] (CH3NH3)PbI3+RCOOH→(CH3NH3)Pb(RCOO)I2+HI.
[0089] It can be understood that when the perovskite material in the modification layer 20 reacts chemically with the ligand in the inorganic nanoparticle layer 30, it is equivalent to the perovskite material and the ligand being connected by chemical bonds, so that the modification layer 20 and the inorganic nanoparticle layer 30 can be firmly connected together. Since the modification layer 20 is tightly adsorbed on the inorganic nanoparticle layer 30, the gap in the inorganic nanoparticle layer 30 can be filled, thereby solving the gap defect problem of the inorganic nanoparticle layer 30, improving the density and flatness of the inorganic nanoparticle layer 30, and then improving the electrical performance of the light-emitting device.
[0090] Exemplarily, the inorganic nanomaterial is an electron transport material, and the electron transport material includes at least one of a metal oxide, a doped metal oxide, a II-VI semiconductor material, a III-V semiconductor material and an I-III-VI semiconductor material; the metal oxide is selected from at least one of ZnO, BaO, TiO2, and SnO2; the metal oxide in the doped metal oxide is selected from at least one of ZnO, TiO2, and SnO2, and the doping element is selected from at least one of Al, Mg, Li, In, and Ga; the II-VI semiconductor material is selected from at least one of ZnS, ZnSe, and CdS; the III-V semiconductor material is selected from at least one of InP and GaP; the I-III-VI semiconductor material is selected from at least one of CuInS and CuGaS.
[0091] It should be noted that when the inorganic nanomaterial in the inorganic nanoparticle layer 30 is zinc oxide (ZnO), the ligand in the inorganic nanoparticle layer 30 is a raw material used in preparing the zinc oxide nanomaterial or a reaction product produced in the process of preparing the zinc oxide nanomaterial.
[0092] In some embodiments, the thickness ratio of the inorganic nanoparticle layer 30 to the modified layer 20 is (60-80):(1-8). The thickness of the modified layer 20 is controlled to maintain its modification effect on the inorganic nanoparticle layer 30, improve the density and flatness of the inorganic nanoparticle layer 30, and avoid affecting the conductivity of the inorganic nanoparticles.
[0093] It should be noted that the composite film 90 provided in the embodiment of the present application can be applied to optoelectronic devices such as organic light emitting diodes (OLEDs), quantum dot light emitting diodes (QLEDs), and solar cells.
[0094] Please combine Figure 1 The present application also provides a method for preparing a composite film, which can be used to prepare the composite film 90 in any of the above embodiments. The method for preparing the composite film may include:
[0095] Providing a substrate (not shown);
[0096] An inorganic nanoparticle layer 30 is formed on a substrate, wherein the inorganic nanoparticle layer 30 includes an inorganic nanomaterial and a ligand connected to a surface of the inorganic nanomaterial;
[0097] A modification layer 20 is formed on the inorganic nanoparticle layer 30 . The material of the modification layer 20 includes a perovskite material. At least part of the ligands are connected to the modification layer 20 .
[0098] It can be understood that the above text has described in detail the materials and thickness of the inorganic nanoparticle layer 30 and the modification layer 20 , and will not be repeated here.
[0099] Exemplarily, the substrate may be a light emitting device preform.
[0100] Exemplarily, “forming the modification layer 20 on the inorganic nanoparticle layer 30 ” may specifically include: applying a perovskite material solution on the inorganic nanoparticle layer 30 by a spin coating method to form the modification layer 20 .
[0101] Exemplarily, the perovskite material solution includes a perovskite material solution and a first solvent, and the concentration of the perovskite material solution can be 0.3mg / ml to 0.8mg / ml (e.g., 0.3mg / ml, 0.4mg / ml, 0.5mg / ml, 0.6mg / ml, 0.7mg / ml, 0.8mg / ml, etc.), that is, each milliliter (ml) of the perovskite material solution contains 0.3mg to 0.8mg of the perovskite material. Exemplarily, the first solvent can include at least one of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO).
[0102] Exemplarily, “forming the modified layer 20 on the inorganic nanoparticle layer 30 ” may further include: after forming the modified layer 20 , annealing the modified layer 20 , wherein the annealing temperature is 70° C. to 90° C. and the annealing time is 6 minutes to 14 minutes.
[0103] It should be noted that, by annealing the modified layer 20 at a temperature of 70°C to 90°C, the embodiment of the present application can not only volatilize the solvent in the modified layer 20 and promote the curing of the modified layer 20, but also promote the perovskite material in the modified layer 20 to react with the ligand in the inorganic nanoparticle layer 30, thereby modifying the gap defects in the inorganic nanoparticle layer 30 and improving the flatness of the inorganic nanoparticle layer 30, thereby improving the electrical performance of the light-emitting device 100.
[0104] Exemplarily, when the modified layer 20 is annealed, the annealing temperature can be 70°C, 72°C, 75°C, 78°C, 80°C, 82°C, 85°C, 88°C, 90°C, etc., and the annealing time can be 6 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes, etc.
[0105] In some embodiments, the material of the modification layer 20 is methylamine lead iodide (CH3NH3PbI3), the thickness of the modification layer 20 is 2 nm, and when the modification layer 20 is annealed, the annealing temperature is 80° C. and the annealing time is 10 minutes.
[0106] Exemplarily, “forming the inorganic nanoparticle layer 30 on the substrate” may specifically include: applying an inorganic nanomaterial solution on the substrate to form the inorganic nanoparticle layer 30 .
[0107] Exemplarily, the inorganic nanomaterial solution includes an inorganic nanomaterial and a second solvent, and a ligand is connected to the surface of the inorganic nanomaterial.
[0108] Exemplarily, the concentration of the inorganic nanomaterial solution is 20 mg / ml to 40 mg / ml, for example, 20 mg / ml, 23 mg / ml, 25 mg / ml, 28 mg / ml, 30 mg / ml, 32 mg / ml, 35 mg / ml, 38 mg / ml, 40 mg / ml, etc.
[0109] Exemplarily, the second solvent includes at least one of an alcohol compound, N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide and acetonitrile; exemplary, the alcohol compound includes at least one of methanol, ethanol and isopropanol.
[0110] Exemplarily, “forming an inorganic nanoparticle layer 30 on a substrate” further includes: after forming the inorganic nanoparticle layer 30 , annealing the inorganic nanoparticle layer 30 , wherein the annealing temperature is 70° C. to 90° C. and the annealing time is 3 minutes to 8 minutes.
[0111] See also Figure 2 or Figure 3 , the embodiment of the present application provides a light emitting device 100, comprising a bottom electrode 70, an inorganic nanoparticle layer 30, a modified layer 20 and a top electrode 10;
[0112] The inorganic nanoparticle layer 30 is disposed on one side of the bottom electrode 70, and the inorganic nanoparticle layer 30 includes an inorganic nanomaterial and a ligand connected to the surface of the inorganic nanomaterial;
[0113] The modification layer 20 is disposed on the side of the inorganic nanoparticle layer 30 away from the bottom electrode 70 , and the material of the modification layer 20 includes a perovskite material, and at least part of the ligands are connected to the modification layer 20 through chemical bonds;
[0114] The top electrode 10 is disposed on a side of the modification layer 20 away from the inorganic nanoparticle layer 30 .
[0115] See also Figure 2 The bottom electrode 70 is an anode, the top electrode 10 is a cathode, and the light-emitting device 100 further includes a light-emitting layer 40 disposed between the bottom electrode 70 and the inorganic nanoparticle layer 30 .
[0116] See also Figure 3 The bottom electrode 70 is a cathode, the top electrode 10 is an anode, and the light-emitting device 100 further includes a light-emitting layer 40 disposed between the modification layer 20 and the top electrode 10 .
[0117] See also Figure 2 When the bottom electrode 70 is an anode and the top electrode 10 is a cathode, the light-emitting device 100 further includes a hole injection layer 60 and a hole transport layer 50 arranged between the bottom electrode 70 and the light-emitting layer 40, wherein the hole injection layer 60 is arranged close to the bottom electrode 70, and the hole transport layer 50 is arranged close to the light-emitting layer 40.
[0118] See also Figure 3 When the bottom electrode 70 is a cathode and the top electrode 10 is an anode, the light-emitting device 100 further includes a hole injection layer 60 and a hole transport layer 50 arranged between the top electrode 10 and the light-emitting layer 40, wherein the hole injection layer 60 is arranged close to the top electrode 10 and the hole transport layer 50 is arranged close to the light-emitting layer 40.
[0119] Please combine Figure 2 and Figure 3 The light emitting device 100 may further include a substrate 80, and the substrate 80 may be disposed on a side of the bottom electrode 70 away from the light emitting layer 40; Figure 2 As shown, when the bottom electrode 70 is an anode, the light emitting device 100 is a positive device; Figure 3 As shown, when the bottom electrode 70 is a cathode, the light emitting device 100 is an inverted device.
[0120] For example, the light emitting device 100 may be a top emitting device (light is emitted toward the side of the light emitting layer 40 away from the substrate 80 ) or a bottom emitting device (light is emitted from the side of the substrate 80 away from the light emitting layer 40 ).
[0121] By way of example, the material of the substrate 80 may be glass.
[0122] It can be understood that when the inorganic nanomaterial in the inorganic nanoparticle layer 30 is an electron transport material (such as zinc oxide), the inorganic nanoparticle layer 30 is equivalent to an electron transport layer.
[0123] The electron transport layer in the existing electroluminescent device is usually a zinc oxide nanoparticle layer. The preparation method of the zinc oxide nanoparticle layer is usually: first prepare a zinc oxide nanomaterial, then use a spin coating method to form a film of the zinc oxide nanomaterial and dry it to obtain the zinc oxide nanoparticle layer. However, the surface of the zinc oxide nanoparticle layer prepared by the above method will inevitably produce gap defects related to trap states. The gap defects related to trap states refer to the gap positions on the surface of the zinc oxide nanoparticle layer that can adsorb or capture electrons or holes injected therein, and can affect the movement of electrons or holes and the diffusion distance of electrons or holes in each film layer of the electroluminescent device. Therefore, the gap defects related to trap states will cause the electrical properties and carrier transport efficiency of the zinc oxide nanoparticle layer to decrease.
[0124] The light-emitting device 100 provided in the embodiment of the present application, by setting a modification layer 20 on the surface of the inorganic nanoparticle layer 30, can utilize the reaction between the ligands in the inorganic nanoparticle layer 30 and the perovskite material in the modification layer 20, so that at least part of the ligands in the inorganic nanoparticle layer 30 can be connected to the modification layer through chemical bonds, so that the modification layer 20 can be used to fill the gaps in the inorganic nanoparticle layer 30, solve the gap defect problem of the inorganic nanoparticle layer 30, and then improve the flatness of the inorganic nanoparticle layer 30.
[0125] Exemplarily, the material of the hole transport layer 50 includes 4,4'-N,N'-dicarbazolyl-biphenyl (CBP), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine (α-NPD), N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine (TPD), poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)benzidine) (Poly-TPD). 、N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine (DNTPD), 4,4',4'-tri(N-carbazolyl)-triphenylamine (TCTA), 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine (m-MTDATA), poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))] (TFB), poly(N-vinylcarbazole) (PVK) and its derivatives, N,N'-bis(1-naphthyl)-N,N '-Diphenyl-1,1'-biphenyl-4-4'-diamine (NPB), poly(phenylene vinylene) (PPV), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene] (MEH-PPV), poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene] (MOMO-PPV), 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-omeTAD), 4,4'-cyclohexylbis[N,N-di(4- At least one of poly(4-(4-methylphenyl)aniline) (TAPC), 1,3-di(carbazole-9-yl)benzene (MCP), polyaniline, polypyrrole, poly(p-phenylene vinylene), aromatic tertiary amines, polynuclear aromatic tertiary amines, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraarylbenzidine, poly(3,4-ethylenedioxythiophene)-polystyrenesulfonic acid (PEDOT:PSS) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, polyspirofluorene and its derivatives, polythiophene (TPH) and its derivatives.
[0126] Exemplarily, the material of the hole injection layer 60 includes at least one of poly(3,4-ethylenedioxythiophene)-polystyrenesulfonic acid (PEDOT:PSS), copper phthalocyanine (CuPc), 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene (HAT-CN), poly(ethylenedioxythiophene) (PEDOT), a derivative of PEDOT:PSS doped with MoO3 (PEDOT:PSS-MoO3), 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine (m-MTDATA), tetracyanoquinodimethane (F4-TCNQ), a transition metal oxide, and a transition metal sulfide compound. Exemplarily, the transition metal oxide may include MoO x , VO x , WO x CrO x , CuO. For example, the metal sulfide compound may include one or more of MoS2, MoSe2, WS2, WSe2, and CuS.
[0127] Exemplarily, the thickness of the bottom electrode 70 and the top electrode 10 can be 20nm-120nm, for example, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 100nm, 105nm, 110nm, 115nm, 120nm, etc.
[0128] Exemplarily, the thickness of the hole injection layer 60 is 15 nm-25 nm, such as 15 nm, 18 nm, 20 nm, 22 nm, 25 nm, etc.
[0129] Exemplarily, the thickness of the hole transport layer 50 is 20 nm-30 nm, such as 20 nm, 22 nm, 25 nm, 28 nm, 30 nm, etc.
[0130] Exemplarily, the thickness of the light emitting layer 40 is 15 nm-25 nm, for example, 15 nm, 18 nm, 20 nm, 22 nm, 25 nm, etc.
[0131] Exemplarily, the thickness of the inorganic nanoparticle layer 30 is 30 nm-40 nm, such as 30 nm, 32 nm, 35 nm, 38 nm, 40 nm, etc.
[0132] Exemplarily, the thickness of the modification layer 20 is 0.5 nm-3.5 nm, such as 0.5 nm, 1 nm, 1.5 nm, 2 nm, 2.5 nm, 3 nm, etc.
[0133] Exemplarily, the bottom electrode 70 and the top electrode 10 can be independently selected from a doped metal oxide electrode, a composite electrode, a graphene electrode, a carbon nanotube electrode, a metal single substance electrode or an alloy electrode. The material of the doped metal oxide electrode can include but is not limited to indium doped tin oxide (ITO), fluorine doped tin oxide (FTO), antimony doped tin oxide (ATO), aluminum doped zinc oxide (AZO), gallium doped zinc oxide (GZO), indium doped zinc oxide (IZO), magnesium doped zinc oxide (MZO), aluminum doped magnesium oxide (AMO), cadmium doped zinc oxide One or more. The composite electrode is an electrode formed by stacking two or more layers of conductive materials, such as AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, Ca / Al, LiF / Ca, LiF / Al, BaF2 / Al, CsF / Al, CaCO3 / Al, BaF2 / Ca / Al, etc., wherein “ / ” represents a stacked structure, for example, AZO / Ag / AZO represents a composite electrode comprising sequentially stacked AZO layers, Ag layers and AZO layers. The material of the metal single substance electrode may include but is not limited to one or more of silver (Ag), magnesium (Mg), aluminum (Al), gold (Au), gallium (Ga), nickel (Ni), platinum (Pt), iridium (Ir), copper (Cu), molybdenum (Mo), calcium (Ca), and barium (Ba). The alloy electrode includes but is not limited to Au:Mg alloy electrode or Ag:Mg alloy electrode.
[0134] In some embodiments, one of the bottom electrode 70 and the top electrode 10 serving as the anode may be an electrode with a relatively high work function, such as but not limited to one or more of a doped metal oxide electrode with a relatively high work function, a metal single substance electrode with a relatively high work function, and a carbon nanotube electrode; the material of the metal single substance electrode with a relatively high work function may be Ni, Pt, Au, Ag or Ir, etc.
[0135] In some embodiments, one of the bottom electrode 70 and the top electrode 10 serving as the cathode may be an electrode with a relatively low work function, such as but not limited to a metal single substance electrode with a relatively low work function, a composite electrode with a relatively low work function, and an alloy electrode with a relatively low work function; the material of the metal single substance electrode with a relatively low work function may be Ca, Ba, Al, Mg, etc.; the structure of the composite electrode with a relatively low work function may be Ca / Al, LiF / Ca, LiF / Al, BaF2 / Al, CsF / Al, CaCO3 / Al, BaF2 / Ca / Al, etc.; the alloy electrode with a relatively low work function may be Au:Mg or Ag:Mg, etc.
[0136] Exemplarily, the material of the light emitting layer 40 may include at least one of an organic light emitting material and a quantum dot light emitting material.
[0137] Exemplarily, the organic light-emitting material may include, but is not limited to, 4,4'-bis(N-carbazole)-1,1'-biphenyl:tri[2-(p-tolyl)pyridine iridium(III)) (CBP:Ir(mppy)3), 4,4',4"-tri(carbazole-9-yl)triphenylamine:tri[2-(p-tolyl)pyridine iridium (TCTX:Ir(mmpy)), diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, 1,4,7,10-tetra-tert-butyl perylene (TBPe), rubrene derivatives (TBRb), thermally activated delayed fluorescence (TADF) materials, light-emitting materials having hybrid localized-charge transfer (HLCT) excited state characteristics, exciplex light-emitting materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives.
[0138] Exemplarily, the quantum dot luminescent material includes at least one of a single structure quantum dot and a core-shell structure quantum dot. Specifically, the material of the single structure quantum dot, the core material of the core-shell structure quantum dot and the shell material of the core-shell structure quantum dot can each include at least one of a II-VI group compound, a IV-VI group compound, a III-V group compound and a I-III-VI group compound. The II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, Z At least one of nSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, At least one of PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, and the III-V compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNS b, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, and the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2.
[0139] See also Figure 4 , while combining Figure 2 or Figure 3 The present application also provides a method for preparing a light-emitting device, comprising:
[0140] S100 , providing a light emitting device preform, wherein the light emitting device preform includes a bottom electrode 70 .
[0141] Please combine Figure 2 When the bottom electrode 70 is an anode and the top electrode 10 is a cathode, the light emitting device preform further includes a light emitting layer 40 formed on the bottom electrode 70 .
[0142] Please combine Figure 2 When the bottom electrode 70 is an anode and the top electrode 10 is a cathode, the light-emitting device preform may further include a hole injection layer 60 and a hole transport layer 50 , wherein the hole injection layer 60 is disposed close to the bottom electrode 70 , and the hole transport layer 50 is disposed close to the light-emitting layer 40 .
[0143] S200, forming an inorganic nanoparticle layer 30 on a light-emitting device preform, wherein the inorganic nanoparticle layer 30 includes an inorganic nanomaterial and a ligand connected to a surface of the inorganic nanomaterial.
[0144] S300 , forming a modification layer on the inorganic nanoparticle layer 30 , wherein the material of the modification layer 20 includes a perovskite material, and at least part of the ligands are connected to the modification layer 20 through chemical bonds.
[0145] S400 , forming a top electrode 10 on the modified layer 20 to obtain a light emitting device 100 .
[0146] Please combine Figure 3 The bottom electrode 70 is a cathode, the top electrode 10 is an anode, and “forming the top electrode 10 on the modified layer 20 ” may specifically include: forming a light-emitting layer 40 on the modified layer 20 , and forming the top electrode 10 on the light-emitting layer 40 .
[0147] Please combine Figure 3 When the bottom electrode 70 is a cathode and the top electrode 10 is an anode, “forming a top electrode 10 on the modified layer 20 ” may specifically include: forming a hole transport layer 50 on the light-emitting layer 40 , forming a hole injection layer 60 on the hole transport layer 50 , and forming a top electrode 10 on the hole injection layer 60 .
[0148] The materials of the substrate 80 , the modification layer 20 , the inorganic nanoparticle layer 30 , the bottom electrode 70 , the hole injection layer 60 , the hole transport layer 50 , the light emitting layer 40 and the top electrode 10 have been described in detail above and will not be repeated here.
[0149] For example, the bottom electrode 70 and the top electrode 10 can be formed by evaporation or vacuum magnetron sputtering, and the hole injection layer, the hole injection layer 60, the hole transport layer 50, the light-emitting layer 40, the inorganic nanoparticle layer 30 and the electron injection layer can be formed by spin coating.
[0150] For example, after forming the top electrode 10, an evaporation method may be used to form an encapsulation layer on the top electrode 10. In some embodiments, the encapsulation layer may include organic material layers and inorganic material layers that are alternately stacked.
[0151] An embodiment of the present application further provides a display device, comprising the light-emitting device in any of the above embodiments or a light-emitting device manufactured by the manufacturing method in any of the above embodiments.
[0152] Exemplarily, the display device may be a terminal such as a television, a monitor, a mobile phone, a tablet computer, or may be a gaming device, an augmented reality (AR) device, a virtual reality (VR) device, a data storage device, an audio playback device, a video playback device, a wearable device, or other device with a display screen, wherein the wearable device may be a smart bracelet, smart glasses, a smart watch, smart decoration, etc.
[0153] The light emitting device 100 provided in the present application is described in detail below in the form of a specific embodiment.
[0154] Example 1
[0155] like Figure 1 As shown, a light-emitting device 100 is composed of a top electrode 10, a modification layer 20, an inorganic nanoparticle layer 30, a light-emitting layer 40, a hole transport layer 50, a hole injection layer 60, and a bottom electrode 70 which are stacked in sequence, wherein the top electrode 10 is a cathode, the bottom electrode 70 is an anode, the material of the top electrode 10 is Ag, the material of the modification layer 20 is methylamine lead iodine (CH3NH3PbI3), the material of the light-emitting layer 40 is a core-shell structure quantum dot, and the material of the core-shell structure quantum dot is CdZnSe / ZnSe / CdZnS, wherein CdZnSe is the material of the core, ZnSe is the material of the first shell layer close to the core, CdZnS is the material of the second shell layer arranged on the side of the first shell layer away from the core, the material of the hole transport layer 50 is TFB, the material of the hole injection layer 60 is PEDOT:PSS, and the material of the bottom electrode 70 is ITO;
[0156] The method for preparing the light emitting device 100 includes:
[0157] ITO is deposited on the substrate by vacuum magnetron sputtering to form a bottom electrode 70, and the thickness of the bottom electrode 70 is 30 nm;
[0158] PEDOT:PSS is applied on the bottom electrode 70 by spin coating to form a hole injection layer 60, the thickness of the hole injection layer 60 is 20 nm, and the hole injection layer 60 is annealed at a temperature of 150° C. for 30 min.
[0159] TFB is applied on the hole injection layer 60 by spin coating to form a hole transport layer 50. The thickness of the hole transport layer 50 is 25 nm. The hole transport layer 50 is annealed at a temperature of 200° C. for 30 min.
[0160] A quantum dot material is applied on the hole transport layer 50 by spin coating to form a light emitting layer 40, the thickness of the light emitting layer 40 is 20 nm, and the light emitting layer 40 is annealed at an annealing temperature of 80° C. for 5 min.
[0161] A zinc oxide nanomaterial solution is applied on the light-emitting layer 40 by a spin coating method. The zinc oxide nanomaterial solution includes zinc oxide nanomaterial and ethanol. The surface of the zinc oxide nanomaterial is connected with an acetate ligand. The concentration of the zinc oxide nanomaterial solution is 20 mg / ml to 40 mg / ml. An inorganic nanoparticle layer 30 is formed. The thickness of the inorganic nanoparticle layer 30 is 35 nm. The inorganic nanoparticle layer 30 is annealed at a temperature of 80° C. for 5 min.
[0162] A methylamine lead iodine solution is applied on the inorganic nanoparticle layer 30 by a spin coating method. The methylamine lead iodine solution includes methylamine lead iodine and N,N-dimethylformamide. The concentration of the methylamine lead iodine solution is 0.5 mg / ml to form a modified layer 20. The thickness of the modified layer 20 is 2 nm. The modified layer 20 is annealed at a temperature of 80° C. for 10 minutes.
[0163] Silver is deposited on the modified layer 20 by evaporation to form a top electrode 10. The thickness of the top electrode 10 is 100 nm.
[0164] Example 2
[0165] A light emitting device 100 and a preparation method thereof, compared with Example 1, the only difference is that the material of the modification layer 20 is different. In Example 2, the material of the modification layer 20 is methylamine lead fluoride (CH3NH3PbF3).
[0166] Example 3
[0167] A light emitting device 100 and a preparation method thereof, compared with Example 1, the only difference is that the material of the modification layer 20 is different. In Example 3, the material of the modification layer 20 is methylamine lead chloride (CH3NH3PbCl3).
[0168] Example 4
[0169] A light emitting device 100 and a preparation method thereof, compared with Example 1, the only difference is that the material of the modification layer 20 is different. In Example 3, the material of the modification layer 20 is methylamine lead bromide (CH3NH3PbBr3).
[0170] Example 5
[0171] A light emitting device 100 and a preparation method thereof, compared with Example 1, the only difference is that the thickness of the modification layer 20, the annealing temperature and the annealing time are different. In Example 5, the thickness of the modification layer 20 is 0.5 nm, the annealing temperature is 70° C., and the annealing time is 12 minutes.
[0172] Example 6
[0173] A light emitting device 100 and a preparation method thereof, compared with Example 1, the only difference is that the thickness of the modification layer 20, the annealing temperature and the annealing time are different. In Example 6, the thickness of the modification layer 20 is 1.5nm, the annealing temperature is 90°C, and the annealing time is 6 minutes.
[0174] Example 7
[0175] A light emitting device 100 and a preparation method thereof, compared with Example 1, the only difference is that the thickness of the modification layer 20, the annealing temperature and the annealing time are different. In Example 7, the thickness of the modification layer 20 is 2.5nm, the annealing temperature is 75°C, and the annealing time is 14 minutes.
[0176] Example 8
[0177] A light emitting device 100 and a preparation method thereof, compared with Example 1, the only difference is that the thickness of the modification layer 20, the annealing temperature and the annealing time are different. In Example 8, the thickness of the modification layer 20 is 3.5nm, the annealing temperature is 85°C, and the annealing time is 9 minutes.
[0178] Comparative Example 1
[0179] like Figure 5 As shown, a light-emitting device 100' is composed of a top electrode 10, an inorganic nanoparticle layer 30, a light-emitting layer 40, a hole transport layer 50, a hole injection layer 60, and a bottom electrode 70 which are stacked in sequence, wherein the material of the top electrode 10 is Ag, the material of the light-emitting layer 40 is core-shell structure quantum dots, the material of the core-shell structure quantum dots is CdZnSe / ZnSe / CdZnS, the material of the hole transport layer 50 is TFB, the material of the hole injection layer 60 is PEDOT:PSS, and the material of the bottom electrode 70 is ITO;
[0180] The method for preparing the light emitting device 100 includes:
[0181] ITO is deposited on the substrate by vacuum magnetron sputtering to form a bottom electrode 70, and the thickness of the bottom electrode 70 is 30 nm;
[0182] PEDOT:PSS is applied on the bottom electrode 70 by spin coating to form a hole injection layer 60, the thickness of the hole injection layer 60 is 20 nm, and the hole injection layer 60 is annealed at a temperature of 150° C. for 30 min.
[0183] TFB is applied on the hole injection layer 60 by spin coating to form a hole transport layer 50. The thickness of the hole transport layer 50 is 25 nm. The hole transport layer 50 is annealed at a temperature of 200° C. for 30 min.
[0184] A quantum dot material is applied on the hole transport layer 50 by spin coating to form a light emitting layer 40. The thickness of the light emitting layer 40 is 20 nm. The annealing temperature is 80° C. and the annealing time is 5 min.
[0185] A zinc oxide nanomaterial is applied on the light-emitting layer 40 by a spin coating method to form an inorganic nanoparticle layer 30, wherein the inorganic nanoparticle layer 30 includes zinc oxide and acetic acid modified on the surface of the zinc oxide. The thickness of the inorganic nanoparticle layer 30 is 35 nm, the annealing temperature is 80° C., and the annealing time is 5 min.
[0186] Silver is deposited on the inorganic nanoparticle layer 30 by evaporation to form a top electrode 10 . The thickness of the top electrode 10 is 100 nm.
[0187] It can be seen that the difference between Comparative Example 1 and Example 1 is that the light emitting device 100 ′ of Comparative Example 1 does not include the modification layer 20 .
[0188] Performance Testing
[0189] The light emitting devices 100 in Examples 1-8 and the light emitting device 100 ′ in Comparative Example 1 were subjected to performance tests, and the results are shown in the following table.
[0190] serial number <![CDATA[EQE max (%)]]> T95@1000nit(h) Example 1 17 62 Example 2 14 44 Example 3 15 50 Example 4 16 55 Example 5 15 43 Example 6 16 50 Example 7 14 40 Example 8 13 35 Comparative Example 1 13 32
[0191] It should be noted that EQE max EQE stands for External Quantum Efficiency, which indicates the efficiency of a light-emitting device in generating photons from external input electron energy, that is, the ratio of the number of photons output by the device to the number of electrons input. max The higher the value, the more photons the light-emitting device generates, which can make the light-emitting device have higher luminous efficiency. T95@1000nit means the time it takes for the brightness of the light-emitting device to decay from 100% to 95% at a brightness of 1000nit. The larger the T95@1000nit, the longer the service life of the light-emitting device.
[0192] It can be seen from the above table that the EQE of the light emitting device 100 of Examples 1 to 8 of the present application is max The EQE of the light emitting device 100 ′ of Comparative Example 1 is greater than max , indicating that the light-emitting devices 100 of Examples 1-8 of the present application have higher luminous efficiency; T95@1000nit of the light-emitting devices 100 of Examples 1-8 of the present application are all greater than T95@1000nit of the light-emitting device 100' of Comparative Example 1, indicating that the light-emitting devices 100 containing the decorative layer 20 in Examples 1-8 of the present application have longer service life.
[0193] By comparing Examples 1-4, it can be seen that the EQE of the light emitting device 100 of Examples 2-3 is max and T95@1000nit are both less than the EQE of the light emitting device 100 of Example 1. max and T95@1000nit, that is, when the perovskite material in the modification layer 20 is methylamine lead iodide (CH3NH3PbI3), the light emitting device 100 has higher luminous efficiency and longer service life.
[0194] By comparing Example 1 with Examples 5-8, it can be seen that the EQEmax / CE and T95@1000nit of the light-emitting device 100 of Examples 5-8 are both smaller than the EQEmax / CE and T95@1000nit of the light-emitting device 100 of Example 1, that is, when the thickness of the modification layer 20 and the thickness of the inorganic nanoparticle layer 30 are maintained within a certain ratio range, the light-emitting device 100 has higher luminous efficiency and longer service life.
[0195] The composite film and its preparation method, the light-emitting device and its preparation method, and the display device provided in the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the present application. At the same time, for those skilled in the art, according to the ideas of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as limiting the present application.
Claims
1. A composite film, characterized in that: It comprises an inorganic nanoparticle layer and a modification layer which are stacked, wherein the material of the modification layer comprises a perovskite material; The inorganic nanoparticle layer includes an inorganic nanomaterial and a ligand connected to the surface of the inorganic nanomaterial, and at least part of the ligand is connected to the modified layer.
2. The composite film according to claim 1, characterized in that At least part of the ligands are connected to the modification layer via chemical bonds.
3. The composite film according to claim 1, characterized in that The structural formula of the perovskite material is ABX3, wherein A is a monovalent organic cation or a monovalent metal cation, B is a divalent metal cation, and X is a halogen ion; the monovalent organic cation is a methylamine ion or a formamidine ion, the monovalent metal cation is a cesium ion or a rubidium ion, and the divalent metal cation is a lead ion or a tin ion.
4. The composite film according to claim 3, characterized in that: The structural formula of the perovskite material is ABX3, wherein A is a monovalent organic cation, and the monovalent organic cation is a methylamine ion; and / or B is a divalent metal cation, and the divalent metal cation is a lead ion; and / or The structural formula of the perovskite material is CH3NH3PbX3.
5. The composite film according to claim 1, characterized in that The structural formula of the ligand is R-COOH, wherein R is selected from C1-C30 alkyl, C2-C30 alkenyl, C2-C30 alkynyl or aromatic group with 5-40 ring atoms; and / or The ligand includes at least one of acetic acid, propionic acid, butyric acid, valeric acid, oleic acid, lauric acid, myristic acid, palmitic acid and stearic acid.
6. The composite film according to claim 1, characterized in that: The inorganic nanomaterial is selected from at least one of metal oxides, doped metal oxides, II-VI semiconductor materials, III-V semiconductor materials and I-III-VI semiconductor materials; and / or The metal oxide is selected from at least one of ZnO, BaO, TiO2, SnO2; and / or The metal oxide in the doped metal oxide is selected from at least one of ZnO, TiO2, and SnO2, and the doping element is selected from at least one of Al, Mg, Li, In, and Ga; and / or The II-VI semiconductor material is selected from at least one of ZnS, ZnSe and CdS; and / or The III-V semiconductor material is selected from at least one of InP and GaP; and / or The Group I-III-VI semiconductor material is selected from at least one of CuInS and CuGaS.
7. The composite film according to claim 1, characterized in that The thickness ratio of the inorganic nanoparticle layer to the modified layer is (60-80):(1-8).
8. A method for preparing a composite film, characterized in that: include: providing a substrate; forming an inorganic nanoparticle layer on the substrate, wherein the inorganic nanoparticle layer comprises an inorganic nanomaterial and a ligand connected to the surface of the inorganic nanomaterial; A modification layer is formed on the inorganic nanoparticle layer, wherein the material of the modification layer includes a perovskite material, and at least part of the ligands are connected to the modification layer.
9. The method for preparing a composite film according to claim 8, characterized in that: At least part of the ligands are connected to the modified layer via chemical bonds; and / or The structural formula of the perovskite material is ABX3, wherein A is a monovalent organic cation or a monovalent metal cation, B is a divalent metal cation, and X is a halogen ion; the monovalent organic cation is a methylamine ion or a formamidine ion, the monovalent metal cation is a cesium ion or a rubidium ion, and the divalent metal cation is a lead ion or a tin ion.
10. The method for preparing a composite film according to claim 8, characterized in that: The forming of the modified layer on the inorganic nanoparticle layer comprises: applying a perovskite material solution on the inorganic nanoparticle layer to form the modified layer; and / or The perovskite material solution includes a perovskite material solution and a first solvent.
11. The method for preparing a composite film according to claim 10, characterized in that: The concentration of the perovskite material solution is 0.3 mg / ml to 0.8 mg / ml; and / or The structural formula of the perovskite material is ABX3, wherein A is a monovalent organic cation or a monovalent metal cation, B is a divalent metal cation, and X is a halogen ion; the monovalent organic cation is a methylamine ion or a formamidine ion, the monovalent metal cation is a cesium ion or a rubidium ion, and the divalent metal cation is a lead ion or a tin ion; and / or The first solvent includes at least one of N,N-dimethylformamide and dimethyl sulfoxide.
12. The method for preparing a composite film according to claim 10, characterized in that: The forming of the modification layer on the inorganic nanoparticle layer further comprises: after forming the modification layer, annealing the modification layer, the annealing temperature is 70° C. to 90° C., and the annealing time is 6 minutes to 14 minutes.
13. The method for preparing a composite film according to claim 8, characterized in that: The forming of the inorganic nanoparticle layer on the substrate comprises: applying an inorganic nanomaterial solution on the substrate to form the inorganic nanoparticle layer; and / or The inorganic nanomaterial solution comprises an inorganic nanomaterial and a second solvent, and a ligand is connected to the surface of the inorganic nanomaterial; and / or The concentration of the inorganic nano material solution is 20 mg / ml to 40 mg / ml; and / or The second solvent comprises at least one of an alcohol compound, N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide and acetonitrile; and / or The alcohol compound includes at least one of methanol, ethanol and isopropanol.
14. The method for preparing a composite film according to claim 13, characterized in that: The forming of the inorganic nanoparticle layer on the substrate further comprises: after the inorganic nanoparticle layer is formed, annealing the inorganic nanoparticle layer, the annealing temperature is 70° C. to 90° C., and the annealing time is 3 minutes to 8 minutes.
15. A light emitting device, characterized in that: include: bottom electrode; An inorganic nanoparticle layer, disposed on one side of the bottom electrode, the inorganic nanoparticle layer comprising an inorganic nanomaterial and a ligand connected to the surface of the inorganic nanomaterial; A modification layer is disposed on a side of the inorganic nanoparticle layer away from the bottom electrode, wherein the material of the modification layer includes a perovskite material, and at least part of the ligands are connected to the modification layer; A top electrode is disposed on a side of the modified layer away from the inorganic nanoparticle layer; Wherein, the bottom electrode is a cathode, the top electrode is an anode, and the light-emitting device further comprises a light-emitting layer disposed between the modified layer and the top electrode; or The bottom electrode is an anode, the top electrode is a cathode, and the light-emitting device further comprises a light-emitting layer disposed between the bottom electrode and the inorganic nanoparticle layer.
16. The light emitting device according to claim 15, characterized in that: At least part of the ligands are connected to the modified layer via chemical bonds; and / or When the bottom electrode is an anode and the top electrode is a cathode, the light-emitting device further comprises a hole injection layer and a hole transport layer disposed between the bottom electrode and the light-emitting layer, wherein the hole injection layer is disposed close to the bottom electrode and the hole transport layer is disposed close to the light-emitting layer; or When the bottom electrode is a cathode and the top electrode is an anode, the light-emitting device further comprises a hole injection layer and a hole transport layer arranged between the top electrode and the light-emitting layer, wherein the hole injection layer is arranged close to the top electrode, and the hole transport layer is arranged close to the light-emitting layer.
17. The light emitting device according to claim 16, characterized in that: The materials of the hole transport layer include 4,4'-N,N'-dicarbazolyl-biphenyl, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)benzidine), N, N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(N-vinylcarbazole) and its derivatives, N,N'-bis(1-naphthyl)-N,N'- diphenyl-1,1'-biphenyl-4-4'-diamine, poly(phenylene vinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene], poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene], 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene, 4,4'-cyclohexylbis[N,N-di(4-methylphenyl)aniline], 1 , 3-di(carbazole-9-yl)benzene, polyaniline, polypyrrole, poly(p-)phenylene vinylene, aromatic tertiary amines, polynuclear aromatic tertiary amines, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraarylbenzidine, poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, polyspirofluorene and its derivatives, polythiophene and its derivatives; and / or The material of the hole injection layer includes at least one of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid and its derivatives, copper phthalocyanine, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, poly(dioxyethylthiophene), 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine, tetracyanoquinodimethane, transition metal oxides and transition metal sulfur compounds; and / or The cathode and the anode are independently selected from a doped metal oxide particle electrode, a composite electrode, a graphene electrode, a carbon nanotube electrode, a metal single substance electrode or an alloy electrode, the material of the doped metal oxide particle electrode includes one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide, the composite electrode includes AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS or ZnS / Al / ZnS, and the material of the metal single substance electrode includes one or more of Ag, Al, Cu, Mo, Au, Pt, Ca, Mg and Ba; and / or The material of the light-emitting layer includes at least one of an organic light-emitting material and a quantum dot light-emitting material, and the organic light-emitting material includes one or more of 4,4'-bis(N-carbazole)-1,1'-biphenyl:tri[2-(p-tolyl)pyridine iridium(III), 4,4',4"-tri(carbazole-9-yl)triphenylamine:tri[2-(p-tolyl)pyridine iridium, diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, 1,4,7,10-tetra-tert-butyl perylene, rubrene derivatives, thermally activated delayed fluorescence materials, exciplex light-emitting materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives;The quantum dot luminescent material comprises at least one of a single structure quantum dot and a core-shell structure quantum dot, the material of the single structure quantum dot, the core material of the core-shell structure quantum dot and the shell material of the core-shell structure quantum dot each comprise at least one of a II-VI group compound, a IV-VI group compound, a III-V group compound and a I-III-VI group compound, and the II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnS At least one of CdS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, Pb At least one of SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, and SnPbSTe, and the III-V compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, and AlNSb , AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, and the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2. ; 18. A method for preparing a light emitting device, characterized in that: include: Providing a light-emitting device preform, wherein the light-emitting device preform comprises a bottom electrode; forming an inorganic nanoparticle layer on the light-emitting device preform, wherein the inorganic nanoparticle layer comprises an inorganic nanomaterial and a ligand connected to the surface of the inorganic nanomaterial; forming a modification layer on the inorganic nanoparticle layer, wherein the material of the modification layer includes a perovskite material, and at least part of the ligands are connected to the modification layer; forming a top electrode on the modified layer to obtain a light-emitting device; Wherein, the bottom electrode is a cathode, the top electrode is an anode, and forming the top electrode on the modified layer comprises: forming a light-emitting layer on the modified layer, and forming the top electrode on the light-emitting layer; or The bottom electrode is an anode, the top electrode is a cathode, and the light-emitting device preform further includes a light-emitting layer formed on the bottom electrode.
19. The method for preparing a light emitting device according to claim 18, characterized in that: When the bottom electrode is an anode and the top electrode is a cathode, the light-emitting device preform further comprises a hole injection layer and a hole transport layer, wherein the hole injection layer is arranged close to the bottom electrode and the hole transport layer is arranged close to the light-emitting layer; or When the bottom electrode is a cathode and the top electrode is an anode, forming the top electrode on the modified layer includes: forming a hole transport layer on the light-emitting layer, forming a hole injection layer on the hole transport layer, and forming the top electrode on the hole injection layer.
20. A display device, characterized in that: The invention comprises a light-emitting device as described in any one of claims 14 to 17 or a light-emitting device manufactured by the manufacturing method as described in any one of claims 18 to 19.